Did the cyberspace foster the entrepreneurship of women with children in rural China? - Shao, KaiChao; Ma, Ruixue; Zhao, Lulu; Wang, Kai; Kamber, Joseph (Frontiers in Psychology, 2022)
Female-entrepreneurship plays a significantly important role in rural areas of China today. In fact, it is a driving force behind inclusive economic development of the country as a whole. However, notably very little literature out there has focused on the impact of how widespread usage of information technology tools affects the mothers entrepreneurship in the outskirt regions. Here, in this paper, the authors attempt to explore the finer details of such an impact by utilizing the data from the 2017 China Integrated Social Survey; along with the IV-Probit model to explore the transmission mechanism. Interestingly enough, it was discovered that Internet applications and tools do indeed increase entrepreneurship among women with children by a roughly 7.88%. In addition, this paper finds that the utilization of such “InfoTech” promote a continuous progress in entrepreneurship among those women with children who endeavor to start a self-managed enterprise in the less developed areas. Lastly, when looking the analysis of the transmission mechanism, this paper found that the role of Internet-usage in promoting rural mothers entrepreneurship was mainly through three factors – the gender equality effect, the information learning effect, and the financing effect. This accumulated data will be thoroughly presented here in the ensuing sections.